Abnormal coalition of navicular and cuboid - a case report - Gurbachan Singh Gindha; Maneesha Sharma; Manjit Singh (Wolters Kluwer Medknow Publications, 2014)
The flat foot may result from a number of causes, out of which fusion between the adjoining tarsals can be one of the causes. An orthopedic surgeon should be aware of such coalitions. The present case study is a report of abnormal fusion of tarsal bones and the effects of such fusion on the adjoining structures and thereby resulting in difficulty during walking. The case presented here was observed while examining tarsal bones during routine undergraduate teaching. A right sided navicular had on its plantar aspect an abnormal wedge shaped accessory ossified part with a facet on its proximal aspect and a cut edge on its anterolateral aspect, corresponding cut edge was observed in proximo-medial aspect of the cuboid belonging to the same body, proving it to be a bar of bone between Navicular and cuboid. This naviculo- cuboid bar of bone might have resulted from lack of differentiation of mesenchyme.